Economia azul e crescimento econômico: O mar brasileiro em perspectiva - Israel de Oliveira Andrade; Andrea Bento Carvalho; Solange Teles da Silva; Tarin Cristino Frota Mont'Alverne (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The blue economy describes the economic activities related to the sea such as fishing, tourism, maritime transportation, marine renewable energy, naval industry and other marine sectors. In addition, the blue economy field of study considers the sustainable exploitation of natural resources. It is important to highlight that the preservation of the marine environment has a very important role to the blue economy - this is directly linked to the significant increase in demand for sea resources in the last fifty years. Consequently, there is an urgent need for public policies with an integrated ecosystem. Since Brazil has an incipient discussion of the blue economy, this work aims to guide researchers towards understanding the potential and challenges of the Brazilian blue economy.
Keywords: C67; F53; F64; Q01; Q28; Q38; Q53; Q58; 330; blue economy; coastal and marine economies; Blue Amazon; United Nations decade of ocean; sustainable; marine GDP